2012
DOI: 10.3109/03009742.2011.633099
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum levels of high-mobility group box 1 (HMGB1) in primary Sjögren's syndrome

Abstract: Serum HMGB1 levels are increased in pSS patients and more specifically in patients with SSA autoantibodies. There was, however, no correlation of HMGB1 with the SSDAI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 14 publications
0
24
1
Order By: Relevance
“…The authors explained this by interference of anti‐HMGB1 antibodies during ELISA measurement and that anti‐HMGB1 is associated with low serum HMGB1 . However, the present study and several others used the ELISA technique for HMGB1 measurement and did not demonstrate that finding. Another investigation demonstrated that serum HMGB1 levels by Western blot were similar to those measured by ELISA …”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…The authors explained this by interference of anti‐HMGB1 antibodies during ELISA measurement and that anti‐HMGB1 is associated with low serum HMGB1 . However, the present study and several others used the ELISA technique for HMGB1 measurement and did not demonstrate that finding. Another investigation demonstrated that serum HMGB1 levels by Western blot were similar to those measured by ELISA …”
Section: Discussioncontrasting
confidence: 80%
“…Also, serum HMGB1 was found to be significantly increased in patients with juvenile idiopathic arthritis . Several studies have also reported overexpression of serum HMGB1 in adult rheumatic diseases such as SLE, rheumatoid arthritis (RA) and primary Sjögren's syndrome . Moreover, HMGB1 was found to be overexpressed in target organs of different rheumatic diseases, including renal tissue in LN, synovial fluid in JIA and RA and skin in cutaneous lupus …”
Section: Discussionmentioning
confidence: 96%
“…Moreover, HMGB-1 nucleosome complexes released by secondary necrotic cells induce double-stranded DNA autoantibodies in mice (6). Furthermore, Dupire et al found elevated HMGB-1 levels in the sera of SS patients using enzyme-linked immunosorbent assay (ELISA), particularly in subjects with Ro/SSA autoantibodies and active disease (8). Furthermore, Dupire et al found elevated HMGB-1 levels in the sera of SS patients using enzyme-linked immunosorbent assay (ELISA), particularly in subjects with Ro/SSA autoantibodies and active disease (8).…”
Section: Introductionmentioning
confidence: 99%
“…Ek et al have shown that HMGB-1 is also highly expressed in the exocrine glands of patients with SS (7). Furthermore, Dupire et al found elevated HMGB-1 levels in the sera of SS patients using enzyme-linked immunosorbent assay (ELISA), particularly in subjects with Ro/SSA autoantibodies and active disease (8).…”
Section: Introductionmentioning
confidence: 99%
“…In autoimmune diseases like systemic lupus erythematosus (SLE), Sjögren's syndrome and rheumatoid arthritis (RA), it has been documented that serum levels of HMGB1 are increased in patients compared to healthy controls [17][18][19]. In patients with RA, it has been shown that extracellular HMGB1 is present in synovial tissue.…”
Section: Introductionmentioning
confidence: 99%